2019
DOI: 10.3389/fimmu.2019.01660
|View full text |Cite
|
Sign up to set email alerts
|

Nfatc4 Deficiency Attenuates Ototoxicity by Suppressing Tnf-Mediated Hair Cell Apoptosis in the Mouse Cochlea

Abstract: The loss of sensory hair cells in the cochlea is the major cause of sensorineural hearing loss, and inflammatory processes and immune factors in response to cochlear damage have been shown to induce hair cell apoptosis. The expression and function of Nfatc4 in the cochlea remains unclear. In this study, we investigated the expression of Nfatc4 in the mouse cochlea and explored its function using Nfatc4 −/− mice. We first showed that Nfatc4 was expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…In our study, the expression of NFAT3 in OHC nuclei is significantly increased in a timedependent fashion after exposure to moderate PTS noise, in agreement with the notion that the NFAT transcription factor family can be activated by CaN. OHC death, as a consequence of increased nuclear NFAT3, is compatible with an earlier report that application of an NFAT inhibitor on explants attenuates gentamicin-induced hair cell death (Bodmer et al, 2016) and is in line with the recent report showing that Nfatc3 (NFAT3) deficiency in mice attenuates ototoxicity by suppressing TNFmediated hair cell apoptosis (Zhang et al, 2019). NFAT forms a cooperative complex with AP-1 or other bZIP proteins through its binding site (Macián et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the expression of NFAT3 in OHC nuclei is significantly increased in a timedependent fashion after exposure to moderate PTS noise, in agreement with the notion that the NFAT transcription factor family can be activated by CaN. OHC death, as a consequence of increased nuclear NFAT3, is compatible with an earlier report that application of an NFAT inhibitor on explants attenuates gentamicin-induced hair cell death (Bodmer et al, 2016) and is in line with the recent report showing that Nfatc3 (NFAT3) deficiency in mice attenuates ototoxicity by suppressing TNFmediated hair cell apoptosis (Zhang et al, 2019). NFAT forms a cooperative complex with AP-1 or other bZIP proteins through its binding site (Macián et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, a report showed that Nfatc3 (NFAT3) deficiency in mice attenuates ototoxicity by suppressing TNF-mediated hair cell apoptosis (Zhang et al, 2019). In fact, overproduction of both ROS and cytokines has been well documented in noise trauma with loss of OHCs (Yamane et al, 1995;Shi et al, 2003;Yamashita et al, 2005;Fujioka et al, 2006;Le Prell et al, 2007;Dhukhwa et al, 2019;Fetoni et al, 2019;Frye et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that noise-induced increase of TNF- α can be regulated by nuclear factor of activated T cells 4 (Nfatc4), a well-researched transcription factor served as proinflammatory cytokine inducer. Nfatc4 knockout mice show resistance to TNF- α -mediated hair cell apoptosis triggered by intense noise [ 95 ]. Notably, TNF- α is testified to be able to induce calcium influx through ERK-dependent activation of TRPV1.…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…These include agents as N-acetylcysteine, sodium thiosulphate, D-methionine, lipoic acid, ebselen, diethyldithiocarbamate, 4-methylthiobenzoic acid, sodium salicylate, neurotrophin-3, BDNF (Brain-derived neurotrophic factor), flunarizine and NOX3 RNA silencing [57,65]. Under basal conditions, Nfatc4 double knockout mice abrogated TNF-mediated apoptosis in auditory hair cells [66]. In a sudden loss of sensorineural hearing loss, intratympanic or oral administration of steroids was effective in auditory recovery [67].…”
Section: Sensorineural Hearing Lossmentioning
confidence: 99%